IDENTIFIKASI PTERIDOPHYTA DI PIKET NOL PRONOJIWO LUMAJANG SEBAGAI SUMBER BELAJAR BIOLOGI - Miftakhul Jannah; Wahyu Prihanta; Eko Susetyorini (University of Muhammadiyah Malang, 2015)
IDENTIFIKASI PTERIDOPHYTA DI PIKET NOL PRONOJIWO LUMAJANG SEBAGAI SUMBER BELAJAR BIOLOGI Miftakhul Jannah, Wahyu Prihanta, Eko susetyorini. 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail: mifta_cute70@yahoo.co.id ABSTRACT Indonesia has abundant Pteridophyta, because Indonesia has a climate that supports the growth of Pteridophyta. Pteridophyta are found in tropical forests which have abundant sunlight and high humidity. Pronojiwo have characteristics suitable forest for life pteridophyta.This type of research is descriptive research. Research will be conducted in two places, pteridophyta samples implemented Piket Nol Pronojiwo Lumajang and FGD in Mataram Lumajang high school Keywords: Pteridhophyta, Piket Nol Lumajang, FGD